Myocardial and Renal Renin–Angiotensin System Enzyme Activity in Dogs - Emma C. Weitzhandler; Marisa K. Ames; Machelle D. Wilson; Oliver Domenig (Journal of Veterinary Internal Medicine)
ABSTRACT Background Methods to quantify the activity of the tissue renin–angiotensin system (RAS) are needed. Objective To estimate myocardial and renal RAS enzyme activity in postmortem tissues. Animals Convenience sample of 15 purpose‐bred laboratory dogs with experimental heartworm infection (Group 1) euthanized as part of an unrelated study and 22 client‐owned dogs which died or were euthanized for any reason (Group 2). Methods Prospective study where myocardial and renal tissue samples were frozen within 20 min of euthanasia (Group 1) or during routine necropsy exam (Group 2). Homogenized tissues were incubated with spiked angiotensin I or II (AngII) under control and inhibitor conditions to assess relative enzyme contributions to AngII or angiotensin 1–7 formation. Freezing was delayed (2‐ or 7‐h in Groups 1 and 2, respectively) in paired samples, to evaluate the effect of time to freezing on RAS enzyme activity. Results Samples were harvested within 20 min of euthanasia (Group 1) or a median of 21.9 h after death or euthanasia (Group 2). RAS enzymes were active in all samples. The median contribution of angiotensin‐converting enzyme to AngII formation was greater than 88% in all tissues. The 90% confidence limits of the geometric mean of the ratio of the angiotensin production of paired samples in 10/14 (Group 1) and 16/19 (Group 2) experiments met equivalence requirements (lower bound > 0.8 and upper bound < 1.2). Conclusions and Clinical Importance Renin–angiotensin system enzymes are present and active in canine myocardial and renal tissues for greater than 24 h postmortem.